Interpretation and Reconstruction of Traditional Rituals on Semiotic Approach (Shor Rite ‘Shachig’) - T. I. Kimeeva; P. V. Abramova; A. A. Nasonov (Научный диалог)
The position is substantiated according to which the preservation of the rite as an object of ethnocultural heritage in modern conditions is possible through bringing it into a museum state. It is argued that this process should be based on the fixation of the rite during the period of its existence in the natural socio-cultural environment, the results of which were reflected in the field diaries of ethnographers stored in museum archives. The authors point to the main difference between the “inheri tor of tradition” and the “bearer of tradition”, which is the fragmentation and discreteness  of the information available to the latter, which is insufficient to recreate the complex image of the traditional  rite. The potential of the proposed methodology for  interpreting  and  reconstructing   traditional rituals is revealed on the example of the Shor rite ‘Shachig’. The authors analyze modern national-social variations in the interpretation of ethnographic information  about  the  rite  of the first third of the XX century. It is shown that the superficial processing of the information contained in the sources and the incorrect decoding of the codes leads to the transformation of the descriptions of all elements and the material component of the rite. As a scientifically grounded alternative, reconstruction and interpretation of this rite from the standpoint of a semiotic approach is proposed, based on a comprehensive analysis of all its elements (actional, verbal, objective) and considering temporal and local characteristics.